The Figurative Language Used In Ayu Meutia's Poetry Tigress Based On Gibbs & Colston's Theory - Rejeki, Christina Sri; Yulianti, Fitri; Kustantinah, Indri (Universitas PGRI Semarang, 2022)
The purpose of this article is to find the truth of Gibbs Colston theory in Meutia’s poetry and to find out the types of figurative language and the most dominant kind of figurative language in Meutia’s poetry. The study focused figurative language in Meutia’s poetry Tigress. The study used descriptive qualitative method and Gibbs Colston’s theory (2012) is used for identifying the figurative language. The writer chooses six poetries randomly. There are Moonset, Migration, Materialism, Your City, What Your Heart is Not, and Awkward Silence. Gibbs Colston theory (2012) conducted about evaluating the use of metaphors, metonymy, irony, idioms, and proverbs. Gibbs Colston (2012 : 19) state that special feature of figurative language may have much to do with their meaning products as with the cognitive processes used to create those meaning. The result of the study is idiom 1 data, irony 5 data, metaphor 133 data, and metonymy 2 data. Proverbs are not found in this study. Figurative language is found metaphor, metonymy, idiom, and irony. The most dominant figurative language in Poetry Tigress is metaphor. Figurative language in poetry gives sense and beauty to the poem. It helps people to expression, description of something, to make easy people to reference of something, to give inspiration and motivation. Keywords: Figurative Language, Poetry, Poetry Tigress